Local Clothing Purchase Decisions among Students in Palembang under the Influence of Imported Apparel: Lifestyle, Expected Value, and Price Perception through Brand Image - Hamid Halin; Nandan Limakrisna; Agus Setyo Pranowo (CV. Picmotiv, 2025)
This study analyzes the dynamics of local clothing purchasing decisions by students in Palembang amidst the dominance of imported products. Despite the widespread campaign to support domestic products, young consumers' preferences for local products still face challenges. The novelty of this study lies in testing a comprehensive structural model that integrates Lifestyle , Expected Value , and Price Perception as predictor variables, with Brand Image as a mediating variable on Purchase Decisions . Data were collected from 366 student respondents in Palembang and analyzed using Structural Equation Modeling (SEM). The results showed that Brand Image significantly mediated the influence of the three independent variables ( Lifestyle , Expected Value , and Price Perception ) on Purchase Decisions . Empirically, Brand Image has the strongest direct influence on Purchase Decisions (path coefficient 0.390) compared to other variables. This finding confirms that in the context of purchasing local fashion products , price and value factors must be managed through strengthening brand image first. Managerial implications suggest that local producers should prioritize investment in strong branding strategies that align with consumer lifestyles.